HCV regulates TGF-β1 production through the generation of reactive oxygen species in an NFκB-dependent manner - Lin, Wenyu (2010)
BACKGROUND & AIMS: The generation of oxidative stress and TGF-β1 production play important roles in liver fibrogenesis. We have previously shown that HCV increases hepatocyte TGF-β1 expression. However, the mechanisms by which this induction occurs have not been well studied. We explored the possibility that HCV infection regulates TGF-β1 expression through generation of reactive oxygen species (ROS), which act through one or more of the p38 MAPK, ERK, JNK, and NFκB signaling pathways to induce TGF-β1 expression. METHODS AND RESULTS: In this study, we demonstrated using the infectious JFH1 model that HCV induces ROS and TGF-β1 expression. We further found that JFH1 activates the phosphorylation of p38 MAPK, JNK, ERK, and NFκB. Through use of small molecule inhibitors and siRNAs to knock down these pathways, we found that HCV-mediated TGF-β1 enhancement occurs through a ROS-induced and p38 MAPK, JNK, ERK1/2, NFκB-dependent pathway. CONCLUSIONS: These findings provide further evidence to support the hypothesis that HCV enhances hepatic fibrosis progression through the generation of ROS and induction of TGF-β1. Strategies to limit the viral induction of oxidative stress appear to be warranted to inhibit fibrogenesis.